The Role of Saturation Transperineal Biopsy in the Diagnosis of Prostate Cancer in the Era of Targeted Fusion Biopsies - A. A. Keln; A. V. Zyryanov; P. V. Zotov; A. V. Ponomarev; A. S. Surikov; V. G. Znobischev (Креативная хирургия и онкология)
Introduction. One of the biggest problems in the diagnosis of prostate cancer (PCa), which distinguishes it from many other solid tumour conditions, is the difficulty of detecting the tumour using standard imaging techniques. The primary method of diagnosis of PCa, which allows timely treatment, is prostate biopsy. However, under certain clinical situations a saturation biopsy allows a more accurate prediction of the volume and degree of malignancy of the tumour, which can be used to plan the tactics of treatment.Materials and methods. 81 patients were examined, whose mean age was 63.5 ± 7.4. The average volume of the prostate was 59 ± 24.2 cm3 , while the average level of the prostate-specific antigen was 12.5 ± 8.9 ng/ml. All patients underwent at least one transrectal prostate biopsy. The average duration of the transperineal saturation biopsy of the prostate was 25.2 ± 7.4 minutes. The average number of biopsies was 25.Results and discussion. Based on the results of transperineal saturation biopsy, prostate cancer was detected in 34 patients (43.2 %). Adenocarcinoma was detected in all patients with confirmed malignant pathology. Gleason grading was 6 points in 22 (27.1 %) patients, 7 in 9 (9.9 %) and 8 in 4 (4.9 %). Aggressive tumour types (Gleason 7 and 8) corresponded to PIRADS 4 and 5. In PIRADS 2 and 3, 80 % and 50 %, respectively, manifested prostatic adenoma without malignant manifestation. Following radical prostatectomy, the results of a planned morphological conclusion were studied alongside biopsy data. It was determined that in 80.0 % (n = 12) of cases the tumour did not go beyond the prostate capsule and in only 20.0 % (n = 3) of cases was not confined to the prostate. The coincidence of diagnosis based on biopsy results and morphological conclusion was 86.7 %.Conclusion. The study showed that saturation transperineal biopsy is often a reference diagnostic method when, despite the presence of clinical suspicion of PCa, a standard biopsy, including targeted fusion biopsies, fails to provide sufficient information to confirm or exclude PCa. In such situations, the proposed technique provides an alternative approach, with a good frequency of detection of prostate cancer.